Effect of COVID-19 Specific Critical Care Nursing Program on Knowledge and Skills of Nursing Officers in an Apex Level Hospital of Uttarakhand - A Pre-Post Design - ., Vandana; Punjot, Pankaj; Rani, Pushpa; Rao, Shalinee (International Journal of Nursing Research, 2023)
Introduction: COVID-19 was global pandemic during its outbreak and it brought challenges for healthcare workers at every level. The patients were admitted in ICU for critical care and COVID-19 specific nursing care was urge in need. Hence, to keep this background in mind there was specific need of training regarding COVID-19 critical care and the study was conducted on same. Methods: A quantitative research analysis was done on 100 nursing personal who worked in COVID-19 areas. The knowledge was assessed and then training was given followed by reassessment of knowledge and skills. The training included different 12 critical care procedures which were specific to COVID-19 care. Results: The study result showed the significant increase in knowledge from pre-test to post-test 1 and 2. The skill assessment was done for 12 procedures with the OSCE checklist. Nursing officers who performed better in posttest also performed better in OSCE skills assessment. COVID-19 specific critical care training program had a significant impact on knowledge and skills of nursing officers. Conclusion: Evidence based nursing practice on COVID-19 specific critical care training was significantly effective on knowledge and skills of nursing officers. The simulator based training on different critical care procedure helped our nurses for enhancing their knowledge, practice, and skills during patient care.